Group Psychosocial Interventions Following Acquired Brain Injury: A Systematic Review and Meta-analysis of Group Process and Outcomes - McGlashan, Hannah L.; Thompson, Kate; Lam, Michael; Cruwys, Tegan; Walter, Zoe C.; Beadle, Elizabeth; Haslam, Catherine (Neuropsychology review, 2025)
Acquired brain injury can result in disability with direct and indirect consequences for psychosocial functioning. Psychosocial interventions embedded within traditional neurorehabilitation may provide a valuable buffer. While there is evidence of benefits associated with group-based psychosocial interventions, there is no single recommended intervention, despite several different approaches having been trialled. This systematic review aimed to provide a critical appraisal of existing group psychosocial interventions in neurorehabilitation, meta-analyse their efficacy, and explore the contribution of group process to outcomes. Eligible studies were published in English-language peer-reviewed journals and recruited adults with acquired brain injury in receipt of group psychosocial interventions. Outcomes of interest were depression, anxiety, quality of life, emotional distress, community integration, and social support. A systematic search of CINAHL, PsycINFO, Medline, Web of Science and Embase from database inception until 08.07.2024 was conducted. Risk of bias was assessed using the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies. Effect sizes were calculated using Hedges’ g and estimated using a three-level random effects model. Sixty-five studies were included in the systematic review, and 48 were included in the meta-analysis ( n = 2653). There was an overall small effect on psychosocial outcomes (Hedges’ g = 0.24, 95% CIs [0.16, 0.33]), though none of the included studies satisfactorily analysed group process despite 70% of these studies proclaiming their importance. Overall, there were mixed findings across intervention type and significant heterogeneity. Recommendations for future psychosocial group interventions in neurorehabilitation are provided.